2022
DOI: 10.1007/s10546-021-00685-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Commercial Aircraft Meteorological Data to Assess the Heat Budget of the Convective Boundary Layer Over the Santiago Valley in Central Chile

Abstract: The World Meteorological Organization Aircraft Meteorological Data Relay (AMDAR) programme refers to meteorological data gathered by commercial aircraft and made available to weather services. It has become a major source of upper-air observations whose assimilation into global models has greatly improved their performance. Near busy airports, AMDAR data generate semi-continuous vertical profiles of temperature and winds, which have been utilized to produce climatologies of atmospheric-boundary-layer (ABL) hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Point 12 shows the location of the Santiago International Airport (SCEL) base operation site for the commercial airplanes providing the AMDAR vertical profiles of winds and temperature. Detailed description of the AMDAR data for Santiago, their validation and their use to estimate boundary layer heights based on Richardson number computation is presented in [22]. In particular, the comparison of AMDAR profiles with 33 morning radiosondes in Santiago showed almost perfect correlations for temperature and root mean squared deviations smaller than 1 °C in the vertical column below 4000 m AGL, while for winds above 1000 m AGL, correlation coefficients were larger than 0.7, and root mean squared deviations were smaller than 2 m s −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Point 12 shows the location of the Santiago International Airport (SCEL) base operation site for the commercial airplanes providing the AMDAR vertical profiles of winds and temperature. Detailed description of the AMDAR data for Santiago, their validation and their use to estimate boundary layer heights based on Richardson number computation is presented in [22]. In particular, the comparison of AMDAR profiles with 33 morning radiosondes in Santiago showed almost perfect correlations for temperature and root mean squared deviations smaller than 1 °C in the vertical column below 4000 m AGL, while for winds above 1000 m AGL, correlation coefficients were larger than 0.7, and root mean squared deviations were smaller than 2 m s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…AMDAR data are routinely assimilated into global weather forecast models, and their positive impact in model results at the synoptic and larger scales is well documented [23,24]. However, at the ABL scale, where urban air pollution takes place, AMDAR basic data provide valuable information (e.g., boundary layer height, valley-scale stability) that is lost in their assimilation into the relatively low-resolution global models, as has been demonstrated for the Santiago case [22]. AMDAR data have been used to describe ABL climatology at the large [25] and local scales [26], but to our knowledge, their use in support of air pollution analyses is limited, despite their great potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local observational data of wind speed and direction at surface level in the Santiago area is extracted from the Chilean automated meteorological and air quality monitoring network (Ministerio del Medio Ambiente, 2015), which will be abbreviated as SINCA in the continuation of this work, and the Chilean weather service stations (Dirección Meteorológica de Chile, 2019), referred to as DMC thereafter. Wind vertical profiles at hourly frequency in Santiago, for the years 2017 to 2019, are extracted from the Aircraft Meteorological Data Relay (AMDAR) data available for the Santiago airport, as presented and analyzed in Muñoz et al (2022).…”
Section: Observations Reanalysis and Future Scenario Datamentioning
confidence: 99%
“…This locally driven ABL evolution is canonical and it can be disrupted by non-local phenomena, such as advection and subsidence that are associated by meso-or synoptic scales, and are influenced by complex topographies. Muñoz et al (2022) analyzed the ABL dynamics in the semi-arid valley of central Chile using meteorological data gathered at a local airport, radiosondes and reanalysis data. They found that the ABL warming is not only explained by the surface fluxes but also by an intense diurnal subsidence.…”
Section: Introductionmentioning
confidence: 99%